A review about the quaternary upper-plate deformation in the Southern Central Andes (36–38°S): A plausible interaction between mantle dynamics and tectonics. (November 2018) - Sagripanti, Lucía; Colavitto, Bruno; Jagoe, Lucía; Andrés, Folguera; Costa, Carlos
Abstract: Quaternary deformation in the Southern Central Andes between 36° and 38°S is disconnected, noncontinuous and not particularly tracing the main mountain topographic fronts. This pattern contrasts to the one to the north through the Chilean-Pampean flat subduction system, where continuous neotectonic structures develop at the feet of the main active structures. Instead, in the Southern Central Andes, two active deformational systems are developed: a western one acting as an out-of-sequence belt with respect to the eastern-frontal structures developed through Cretaceous and Cenozoic times, and an eastern one associated with different individual structures. While the western deformational belt constitutes the continuation to the north of an intra-arc fault system associated with dip- and strike-slip displacements in a strain partitioned regime, the eastern sector cannot be directly related to other deformational systems neither to the north nor south. However, a strong correlation exists between areas that show evidence of Quaternary deformation and a complex pattern of mantle anomalies affecting the lower lithosphere determined in previous magnetotelluric surveys. We suggest that the thermally weakened crust at these latitudes could be the main control focalizing deformation, which would explain this contrasting pattern of young deformations in the Southern Central Andes. Highlights: Quaternary deformation in the Southern Central Andes (36° - 38°S). Surface and deep structural process are discussed. Fluvial network perturbations associated with active structures. Strong correlation between Quaternary deformation and complex pattern of mantle anomalies.